RESPON PENDAYAGUNAAN AIR PANAS DAN LILIN LEBAH TERHADAP PENGHAMBATAN PENYAKIT ANTRAKNOSA PADA BUAH JAMBU BIJI (Psidium guajava L). - Mia Yasinta Bangun; Swati Sembiring; Julieta Christy (Universitas Quality, 2022)
Guava is one of the fruits that easily rot after postharvest. With the nature of guava that is easy to rot, it is necessary to find a way to maintain the quality of guava by extending its shelf life and freshness. The purpose of this study was to determine the effect of hot water treatment on the control of anthracnose in guava, to determine the effect of beeswax treatment on the control of anthracnose in guava and to determine the effect of hot water treatment with beeswax to maintain the quality of guava fruit. The experimental design used in this study was a completely randomized design using 5 treatments. The first treatment was control treatment, that is, without any treatment. The second treatment used a concentration of 4% beeswax and 5 minutes of hot water immersion. The third treatment was using a concentration of 4% beeswax and 10 minutes of hot water immersion. The fourth treatment was using a concentration of 6% beeswax with 5 minutes of hot water immersion. The fifth treatment was using a concentration of 6% beeswax and 10 minutes of soaking. The treatment was repeated three times. The results of this study showed that the best treatment in inhibiting anthracnose on guava fruit was with a concentration of 6% beeswax and 10 minutes of immersion with 30% of disease attack.